First Name Popularity as Predictor of Employability. (March 2015) - Pascual, Alexandre; Guéguen, Nicolas; Vallée, Boris; Lourel, Marcel; Cosnefroy, Olivier
<x content-type="archive" xml:space="preserve">Abstract</x> For more than fifty years, research in psychology has demonstrated that our evaluation of others may be influenced by their surname or first name. In this study, we evaluated the impact of the attractiveness and frequency of names in situations of recruitment for low qualification level jobs. Using data from a recruitment agency, we tested (binomial regression) for effects associated with first name popularity, surname frequency, first name + surname attractiveness, ethnicity, gender, and age on job interview outcome of 507 low qualified French persons. The logistic regression analysis indicated that, among the various variables tested, first name popularity remained the best predictor of employability.